STUDY ON THE COMPOSITION AND SINGING CHARACTERISTICS OF CHINESE ANCIENT POETRY CHORAL WORKS (Journal of Creative Industry and Sustainable Culture, 2024)
ABSTRACTThe study of the creation and singing characteristics of ancient poetic choral works involves the study of ancient poetic art, choral art, harmonic composition, song singing, conducting techniques and artistic development, which is a very challenging research topic. This is mainly due to the special characteristics of the subject matter itself. As an art that encompasses a wide range of subjects, chorus itself has many characteristics in terms of connotation and extension. As the most important element of choral art, the combination of choral composition and singing characteristics can emphasize the characteristics and style of choral art. The main purpose of this study is to analyze the choral works of ancient poems composed since the emergence of Chinese choral art, organize them into categories, then analyze their characteristics, and then summarize the corresponding singing characteristics of different styles, periods and genres, so as to come up with a complete system of ancient poems composition and singing characteristics. By combining qualitative research with quantitative research and through interviews with experts, the various weaves of this system are further refined. The results of this study will help to present some innovative ideas and help in the current field of Chinese ancient poetry choral works. It will be of some guidance to some scholars engaged in the art of mass choral singing as well as introductory choral conducting.